2020
DOI: 10.21037/jtd-20-2066
|View full text |Cite
|
Sign up to set email alerts
|

Identification of microRNAs enriched in exosomes in human pericardial fluid of patients with atrial fibrillation based on bioinformatic analysis

Abstract: Background: Atrial fibrillation (AF) is related to structural and electrical atria remodeling. Atrial fibrosis development and progression is characteristic of structural remodeling and is taken as the AF perpetuation substrate. Increasing evidence has confirmed that microRNAs (miRNAs) are associated with AF, including cardiac fibrosis. Methods: Pericardial fluid (PF) samples were collected from nine adult patients who had congenital heart disease with persistent AF or sinus rhythm (SR) undergoing surgery. Abn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…These miRNAs targeted pathways related to atrial function and structure, oxidative stress, and fibrosis [ 231 ]. Similarly, EVs from pericardial fluid of atrial fibrillation patients contained 31 downregulated miRs and 24 upregulated miRs, the latter of which included miR-382-3p, -2136-5p, and 450a-2-3p which are predicted to target multiple fibrosis-related genes [ 232 ]. Plasma exosomes from heart failure patients contained elevated levels of miR-21 and reduced levels of miR-425 and miR-744 and these miRs regulated fibrogenic pathways in cardiomyocytes [ 173 , 233 ].…”
Section: Cardiac Fibrosismentioning
confidence: 99%
“…These miRNAs targeted pathways related to atrial function and structure, oxidative stress, and fibrosis [ 231 ]. Similarly, EVs from pericardial fluid of atrial fibrillation patients contained 31 downregulated miRs and 24 upregulated miRs, the latter of which included miR-382-3p, -2136-5p, and 450a-2-3p which are predicted to target multiple fibrosis-related genes [ 232 ]. Plasma exosomes from heart failure patients contained elevated levels of miR-21 and reduced levels of miR-425 and miR-744 and these miRs regulated fibrogenic pathways in cardiomyocytes [ 173 , 233 ].…”
Section: Cardiac Fibrosismentioning
confidence: 99%
“…Previously, miR‐3,126‐5p was shown to function as a diagnostic marker of hepatocellular carcinoma 23 . Another study revealed that miR‐3,126‐5p was differentially expressed in patients with atrial fibrillation 32 . Moreover, a study conducted by Azuma Y et al 33 showed that miR‐3,126‐5p participated in the process of gefitinib‐resistant lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The studies of Wei et al and Liu et al are similar. The former study showed that expression of miR-92b-3p, miR-1306-5p and miR-let-7b-3p are different in patients with AF compared to those with normal sinus rhythm ( 55 ), while the latter identified miR-382-3p as a differentially expressed miRNA ( 56 ). The study of Mun et al attempted to identify specific biomarkers for persistent AF.…”
Section: Diagnostic and Therapeutic Role Of Exosomes In Atrial Fibrillationmentioning
confidence: 99%
“…The following miRNAs have been shown to appear in exosomes and contribute to the diagnosis of AF: miR-483-5p, miR-142-5p, miR-223-3p, miR-223-5p, miR-92b-3p, miR-1306-5p and miRlet-7b-3p, miR-382-3p, miRNA-103a,−107,−320d,−486, and let-7b (50,(54)(55)(56).…”
Section: Microrna In the Diagnosis Of Atrial Fibrillationmentioning
confidence: 99%